ONE-POT SYNTHESIS OF ISOQUINUCLIDINE DERIVATIVES THROUGH MULTICOMPONENT AZA-DIELS-ALDER REACTIONS PROMOTED BY NIOBIUM PENTAETHOXIDE - Sacoman Torquato da Silva, Bruno Henrique [UNESP]; Luiz Carlos da Silva-Filho, Lucas Michelao Martinsand [UNESP] (Raman Publ, 2015)
The bicyclic isoquinuclidine system can be found in many natural products and has several pharmacological properties. In this paper is described an one-pot sysnthesis of Isoquinuclidine derivatives through multicomponent aza-Diels-Alder reactions between aniline derivatives, benzaldehyde and 2-cyclohexenone, promoted by niobium pentaethoxide under mild conditions, affording the expected products in high yields.
Keywords: Isoquinuclidine derivatives; Niobium pentaethoxide; multicomponent reaction; aza-Diels-Alder; Lewis acid